Intrinsic Efficiency Calibration for Uranium Isotopic Analysis in Soil Samples - Loat, Bui Van; Leuangtakoun, Somsavath; Luu, Cao Dang; Hong, Bui Thi; Khang, Khong Nam; Nghia, Nguyen The; Ha, Nguyen Hong; Duyen, Vu Thi Kim (VNU Journal of Science: Mathematics - Physics, 2017)
Abstract:   In this work, we present the results of using the non-destructive gamma spectroscopic method for uranium isotopic analysis and checking the status of radioactive equilibrium between 238 U and 226 Ra in soil samples. In order to analyze uranium isotopes and check the status of equilibrium between 238 U and 226 Ra the activity ratios 235 U/ 238 U and 238 U/ 226 Ra were measured. The these activity ratios were determined based on the characteristic gamma rays and using intrinsic (relative) detection efficiency calibration method. The results obtained shows that this suggested analytical method can be used to determine the uranium concentration in the case of the samples having arbitrary shapes and it does not require the use of any reference materials.